The introduction and spread of rye (Secale cereale) in the Iberian Peninsula - Seabra, Luís (2023)
Some of the earliest Western European macroremains of rye (Secale cereale) have been recently recovered in Northwest Iberia. However, the chronological and cultural contexts of these remains have not been yet exhaustively analysed. To address this gap of research, previous and unpublished assemblages have been reviewed and analysed through an analytical set of methods: biometry, radiocarbon dates and integrating the remains of rye in the broad archaeobotanical record of the region. Results show the earliest macroremains of rye in the Iberian Peninsula date to a period between the 3rd century and the first half of the 1st century BCE. Rye was usually found in assemblages dominated by spelt and other cereals, in whose fields it was likely acting as a weed. There is no record of rye for about the two following centuries, after which it is probably reintroduced, now as a crop. It is found in several sites from the 3rd-4th centuries CE onwards, suggesting it is a staple crop as in other regions in Europe. Significant differences in grain size are only recorded in a 10th-11th century settlement, suggesting few changes in grain morphometry before Medieval times.